The Engineering of Fruit Picker Tool - Muhammad Yandriza Fanni; Saipul Bahri Daulay; Sulastri Panggabean (Universitas Sumatera Utara, 2013)
This study is about designing fruit picker tool. The research was underway to design, build and test melinjo fruit picker tool in its plants. The parameters measured were the capacity of the tool, the percentage of defects, and economic analysis. The research was conducted in Tridharma, A. H. Nasution and Bunga Mawar Roads on the road from February to August 2012. The results showed that the effective tool capacity was 12.22 kg hour-1. Percentage of defect was 4.6%. The economic analysis was Rp 427.58 kg-1, the BEP was Rp 4687.6085 kg year-1 and the IRR was 62.22%.